The Berlin Reader A Compendium on Urban Change and Activism - Bernt, Matthias; Grell, Britta; Holm, Andrej (Urban Studies, 2013)
By drawing together widely dispersed yet central writings, the Berlin Reader is an essential resource for everyone interested in urban development in one of the most interesting and important metropolises in Europe. It provides scholars as well as students, journalists and visitors with an overview of the most central discussions on the tremendous changes Berlin experienced since the fall of the wall. It covers a wide range of issues, including inner city renewal, housing and the local economy, gentrification and other urban conflicts. The book breaks ground in two dimensions: first, by offering also non-German speakers an insight into the very controversial debates after reunification, and, second, by highlighting the ambivalent consequences of Berlins urban transformation in the past decades.